Solid-Phase Microextraction - Tzanavaras, Paraskevas D. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book covers the most recent research activities and achievements regarding to the solid phase microextraction (SPME) technique. It is a powerful sample preparation tool that addresses the new challenges of analytical laboratories. Among others, its fundamental applications involved the sampling of volatile compounds from various matrixes. The demonstrated topics ranged from aroma characterization of various fruits, essential oils to the utilization of SPME for in-tube extraction and isolation of selected compounds from complex samples followed by state-of-the-art analytical techniques.